COMPARATIVE STUDY OF WASTEWATER KNOWLEDGE TOWARDS SUSTAINABLE INFRASTRUCTURE: A CASE STUDY OF GERMANY AND INDONESIAN UNIVERSITY STUDENTS - Ayomi Dita Rarasati; Raihan Alisha Nabila; Jachrizal Sumabrata; Sultan Rianto (Simposium II UNIID 2017, 2017)
Knowledge is transferred in order to run specific goals. Sustainable wastewater infrastructure plays a significant role to the human needs especially the demand for clean and safe water. People’s knowledge will also influence the process of treating water to be discharged to water bodies that support the sustainable wastewater infrastructure in Germany and Indonesia. The focus respondents in this research are the university students in Germany and Indonesia who are considered to have a capability to gain and implement specific knowledge. Survey was conducted to indicate how well the university students know about the wastewater knowledge, the knowledge transfer occurrence, and the correlation of some variables such as study background, degree program, and nationality of the university students with wastewater knowledge and knowledge transfer occurrence to support the sustainable wastewater systems and infrastructures in Germany and Indonesia. The wastewater knowledge of university students in Germany and Indonesia is still low and the correlation of some variables such as study background, degree program, and nationality of the University students with wastewater knowledge and knowledge transfer occurrence are still considered low.